2003
DOI: 10.1046/j.1460-9568.2003.02812.x
|View full text |Cite
|
Sign up to set email alerts
|

Homer‐1a/Vesl‐1S enhances hippocampal synaptic transmission

Abstract: Homer/Vesl proteins are involved in regulating metabotropic glutamate receptors, synaptogenesis, dendritic spine development and axonal pathfinding. We investigated the potential modulation of glutamatergic synaptic transmission by the immediate early gene product Homer-1a/Vesl-1S and by the constitutively expressed long-form Homer-1c/Vesl-1L in CA1 pyramidal cells from cultured rat hippocampal slices. Semliki Forest virus vector-mediated overexpression of Homer-1a enhanced alpha-amino-3-hydroxy-5-methyl-4-iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 44 publications
1
39
1
Order By: Relevance
“…We found that overexpression of Homer-1a enhanced AMPA receptor function and clustering, whereas it affected neither NMDA receptor function and clustering nor presynaptic glutamate release (53). In contrast to Homer-1a, Homer-1c overexpression did not alter synaptic transmission.…”
Section: Spine Maturation and Synaptic Functioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We found that overexpression of Homer-1a enhanced AMPA receptor function and clustering, whereas it affected neither NMDA receptor function and clustering nor presynaptic glutamate release (53). In contrast to Homer-1a, Homer-1c overexpression did not alter synaptic transmission.…”
Section: Spine Maturation and Synaptic Functioncontrasting
confidence: 57%
“…our previous study (53) that Homer-1a promotes AMPA receptor insertion at both functional synapses (containing AMPA and NMDA receptors) and previously silent synapses (expressing only NMDA receptors; Fig. 3).…”
mentioning
confidence: 72%
“…NMDA receptor glutamatebinding chain (Grina) was upregulated, but only in the EC during the chronic phase. The only glutamate signaling molecule that was acutely upregulated was Vesl/homer, which appears to play a role in synaptic potentiation (Hennou et al, 2003). Increased expression of homer1a, however, has some antiepileptogenic effects as shown in kindled mice with overexpression of homer1a (Potschka et al, 2002).…”
Section: Glutamate Signalingmentioning
confidence: 99%
“…13 Transduction of primary neurons and hippocampal slice cultures has allowed studies on protein transport and localization as well as functional activity, typically by electrophysiological recordings. 14 Moreover, alphavirus vectors have been applied for in vivo administration in the rodent brain. Injection of SIN vectors expressing b-galactosidase into the mouse nucleus caudatus/putamen and nucleus accumbens septi resulted in neuron-specific reporter gene expression.…”
Section: Neurosciencementioning
confidence: 99%